2020
DOI: 10.1177/1934578x20911255
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Chemical Structures From Cortex Lycii, Based on Manual and Automatic Analysis of the HPLC-Q-TOF-MS Data

Abstract: Cortex Lycii, the root barks of Lycium barbarum and L. chinense, known as “di gu pi” in traditional Chinese herbal drugs, is an important ingredient of formulations used for treating a variety of diseases. During the last 3 decades, more than 70 chemical entities have been separated and purified from either the aqueous or aqueous ethyl alcohol extracts of Cortex Lycii. In this study, high-performance liquid chromatography together with quadrupole-time-of-flight mass spectrometry (MS) was employed to explore ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…After being harvested in early spring or after autumn, the roots are washed, stripped of the root bark, and dried. Modern research shows that the roots of goji berry is rich in a variety of terpenoids, sterols, phenols, phenylpropanoids, alkaloids, cyclic peptides, and other active ingredients (Chen et al., 2019 ; Jiang et al., 2020 ). Li et al., ( 2020 ) analyzed the quality of Cortex Lycii between different origins using kukoamines as the main evaluation index results showed that there were significant differences.…”
Section: Plant‐based Goji Berry By‐products and Their Utilizationmentioning
confidence: 99%
“…After being harvested in early spring or after autumn, the roots are washed, stripped of the root bark, and dried. Modern research shows that the roots of goji berry is rich in a variety of terpenoids, sterols, phenols, phenylpropanoids, alkaloids, cyclic peptides, and other active ingredients (Chen et al., 2019 ; Jiang et al., 2020 ). Li et al., ( 2020 ) analyzed the quality of Cortex Lycii between different origins using kukoamines as the main evaluation index results showed that there were significant differences.…”
Section: Plant‐based Goji Berry By‐products and Their Utilizationmentioning
confidence: 99%
“…Therefore, it is necessary to comprehensively and objectively evaluate the chemical constituents of A. kusnezoffii Reichb. Due to the rapid development of bio-information technology and MS analysis technology for complex chemical components of traditional Chinese medicine in recent years, the molecular network method based on MS/MS data analysis has become a key project of our laboratory [21][22][23][24]. In this context, molecular networking, based on the HPLC coupled with quadrupole TOF-MS/MS (HPLC-Q-TOF-MS/MS) data analysis, was introduced to investigate the whole diterpenoid alkaloids, which resulted in the identification of 33 diterpenoid alkaloids based on the known nine diterpenoid alkaloids nodes by molecular networking from water extracts.…”
Section: Introductionmentioning
confidence: 99%